Risk factors for Crimean-Congo Haemorrhagic Fever (CCHF) virus exposure in farming communities in Uganda. Issue 6 (December 2022) - Atim, Stella A.; Ashraf, Shirin; Belij-Rammerstorfer, Sandra; Ademun, Anna R; Vudriko, Patrick; Nakayiki, Teddy; Niebel, Marc; Shepherd, James; Balinandi, Stephen; Nakanjako, Gladys; Abaasa, Andrew; Johnson, Paul C.D.; et al.
Highlights: Risk factors for zoonotic transmission of Crimean-Congo Haemorrhagic fever Virus (CCHFV) among livestock farming communities in Uganda. Extremely high CCHFV seroprevalence was detected in humans and domestic animals in Uganda The burden of CCHFV infection and risk factors has to date been underestimated in Uganda. Detection of CCHV in multiple pools of Rhipicephalus appendiculatus suggest these ticks to be the likely vectors for CCHFV in Uganda CCHFV risk in humans were associated with livestock rearing, age and collecting/ eating ticks Further work is indicated to estimate the incidence of CCHFV infection as a cause of non-malarial fever Abstract: Background: Crimean-Congo Haemorrhagic Fever (CCHF) is an emerging human-health threat causing sporadic outbreaks in livestock farming communities. However, the full extent and the risks associated with exposure of such communities has not previously been well-described. Methods: We collected blood samples from 800 humans, 666 cattle, 549 goats and 32 dogs in districts within and outside Ugandan cattle corridor in a cross-sectional survey, and tested for CCHFV-specific IgG antibodies using Enzyme-Linked Immunosorbent Assays. Sociodemographic and epidemiological data were recorded using structured questionnaire. Ticks were collected to identify circulating nairoviruses by metagenomic sequencing. Results: CCHFV seropositivity was in 221/800 (27·6%) in humans, 612/666 (91·8%) in cattle, 413/549 (75·2%) in goats and 18/32 (56·2%) in dogs. Human seropositivity was associated with livestock farming (AOR=5·68, p<0·0001), age (AOR=2·99, p=0·002) and collecting/eating engorged ticks (AOR=2·13, p=0·004). In animals, seropositivity was higher in cattle versus goats (AOR=2·58, p<0·0001), female sex (AOR=2·13, p=0·002) and heavy tick infestation (>50 ticks: AOR=3·52, p=0·004). CCHFV was identified in multiple tick pools of Rhipicephalus appendiculatus . Interpretation: The very high CCHF seropositivity especially among livestock farmers and multiple regional risk factors associated exposures, including collecting/eating engorged ticks previously unrecognised, highlights need for further surveillance and sensitisation and control policies against the disease.